Impact of loss of confidence in the UK on the domestic and global economy - Muhammad Rheza Ramadhan (Journal of Enterprise and Development (JED), 2023)
Purpose — This research examines the effects of loss of confidence caused by tax cuts in the UK on the domestic and worldwide economies.Method — The G-Cubed model is used to simulate a 5% shock to risk premiums in the UK. G-Cubed is a multi-country, multisector, intertemporal general equilibrium model used to analyse a range of policies in international commerce, tax reform, and environmental regulation. Combining the finest elements of three study fields—econometric general equilibrium modelling, international trade theory, and contemporary macroeconomics—is intended to close the gaps between them.Result — UK currency surplus in non-shocked nations leads to exchange rate decline and capital flight, reducing the capital stock and raising interest rates. Loss of confidence prompts households to discount income, resulting in lower domestic consumption and increased savings, coupled with a decrease in private investment. The UK currency's decline improves net exports but eventually causes a drop in real GDP, with falling investment and consumption exceeding rising net exports. Capital outflows and depreciation lead to inflation, mainly in the short term. However, capital outflows from the UK benefit non-shocked countries by raising capital, investment, capital stock, consumption, and real GDP.Contribution — The present study contributes to the academic literature by offering novel insights into the impact of loss of confidence caused by tax cuts on the economies in both, the UK and other countries, by employing G-Cubed model.